Mia Mia Aboriginal Community Development: Fostering Cultural Security - Kickett-Tucker, Cheryl; Bessarab, Dawn; Coffin, J.; Wright, Michael (Cambridge University Press, 2016)
Until recently, Aboriginal people have been subjected to mainly top-down development, which has proven damaging to communities. Mia Mia Aboriginal Community Development offers an alternative to such approaches, promoting cultural security in order to empower Aboriginal people to strengthen their own communities. The authors take a multidisciplinary approach to the topics of Aboriginal community development, Aboriginal history, cultural security and community studies. This book includes chapters examining historical and contemporary Aboriginal conceptions of community development, and the effects of post-structuralism, post-modernism, globalisation and digital technology. As well as comprehensive analysis of community development in Aboriginal communities, it presents practical strategies and tools for improvement. Each chapter includes practical case studies and review exercises, encouraging active learning and reflection. A valuable resource for tertiary education students, this book features contributions from some of Australia's most eminent Aboriginal scholars, Elders and Aboriginal community members alongside contributions from community development practitioners.